THE AUTHORITY OF THE ALTERNATIVE DISPUTE RESOLUTION AGENCIES IN THE INSURANCE SECTOR UNDER INDONESIAN LAWS - Elisatris Gultom; Siti Rohani; Huta Disyon; Savirra Satriadi (Kanun Jurnal Ilmu Hukum, 2023)
This study examines the mechanism and authority involved in resolving consumer disputes within the insurance sector. The study adopts a normative juridical method to analyze the topic comprehensively. Initially, it provides an overview of the mechanism employed to address consumer disputes in the insurance sector. Subsequently, it delves into an examination of the authority responsible for handling such disputes in Indonesia, particularly focusing on out-of-court alternative dispute resolution methods. The findings of the study reveal that insurance customers resort to various dispute resolution measures when faced with claim defaults by insurance companies. These measures include initiating civil lawsuits in the District Court and filing reports through either the Consumer Dispute Settlement Agency or the Indonesian Insurance Mediation Agency. It is important to note that the resolution of insurance disputes should adhere to the terms and conditions outlined in the Insurance Policy, as it represents a binding agreement between the insurer and the insured